Influence of Geographic Region on Fatty Acid and Physical Properties of Indonesian Cocoa Butter from Smallholder Estate - Hendy Firmanto; Supriyanto Supriyanto; Sri Anggraheni; Agung Wahyu Susilo; Bayu Setyawan (Indonesian Coffee and Cocoa Research Institute, 2019)
Cocoa butter is the most essensial component in chocolate formulation and represent the biggest characteristic of this product. Indonesia is the third cocoa producers with cocoa producing area spread out in different geographic region and may affect in cocoa butter profiles. The aim of this experiment was to evaluate the fatty acid characteristic and physical properties of cocoa butter from smallholder estate relate to geographic region and climate. This experiment was conducted using unfermented cocoa bean from smallholder estate in eight provinces of Indonesian most growing areas. Fatty acid composition evaluated through the different region and physical properties evaluated in melting profiles and solid fat content. The result explain the fatty acid characteristic of Indonesian cocoa butter consist of palmitic acid (C16:0) 26.28–29.20%, stearic acid (C18:0) 32,14–37.29% and oleic acid (C18:1) 32,14–37,29%. Growing temperature signifi- cantly affects the increase of palmitic acid composition contribute to cocoa butter hardness. Cocoa butter completely melt in temperature of 36.65–39.20OC and solid fat content ranged 7.288–16.82% in 33OC and ranged 0.02–0.29% in 38OC. This Indonesian cocoa butter comply to the classification of hard cocoa butter.